The Effect of Anairabic High by Intensine perjodic Technique on same Bsachemical variables and (110) Hurdles sprint performance in Anbar province - Ibrahim, Khalil; Baher, Abdullah (Journal of Physical Education, 2008)
The present study aimed at exploring the effect of anairabc tranings on some biochemical variables in blood and the level of performance in 110 hurdles sprints -The study was carried out at a sample of Anbar province Track and Field Team in (110) hurdles sprint skill. They were 4 in number . preperformance measurement of members of the sample in addition to the selection of biochemical variables such as calcium , potassium , sodium , cruiatur , phosphates and phosphocainise were taken by the specialized working team following the proper scientific procedures . The training program designed by the researchers was applied for (8) weeks of (6) training seasons poor week using the highly periodic technique (80-90%) of the optined individual energy . postperformance tests were carried out using the same technique adopted in preperformace tests . Data and results were collected and statistically processed . Then , they were introduced in tables and analysed and discussed in a scientific mithodologys referring to scientific sowerces . Results have shown that was aerial traininge of highly intensium periodic technique led to an important in the concertration of biochemical variables under study , in addition to an improvement in the performance of (110) hurdles sprints athletes . The researchers recommended the use of this approach to improve the performance of (110) sprinters . They advocated the use of biochemical variables measurement as a style for the continuaus evaluation of the training and physiological conditions of the athelets to arrive at optined results